Boosting Near‐Infrared Luminescence of Lanthanide in Cs2AgBiCl6 Double Perovskites via Breakdown of the Local Site Symmetry. (8th June 2022) - Pei, Yifan; Tu, Datao; Li, Chenliang; Han, Siyuan; Xie, Zhi; Wen, Fei; Wang, Luping; Chen, Xueyuan
Abstract: Currently, lanthanide (Ln 3+ )‐doped near‐infrared (NIR)‐emitting double perovskites (DPs) suffer from low photoluminescence quantum yield (PLQY). Herein, we develop a new class of NIR‐emitting DPs based on Ln 3+ ‐doped Cs2 (Na/Ag)BiCl6 . Benefiting from the Na + ‐induced breakdown of local site symmetry in the Cs2 AgBiCl6 DPs, effective NIR emissions of Ln 3+ are realized through Bi 3+ sensitization. Specifically, 7.3‐fold and 362.9‐fold enhanced NIR emissions of Yb 3+ and Er 3+ are achieved in Cs2 Ag0.2 Na0.8 BiCl6 DPs relative to those in Na‐free Cs2 AgBiCl6 counterparts, respectively. The optimal absolute NIR PLQYs for Yb 3+ and Er 3+ in Cs2 Ag0.2 Na0.8 BiCl6 DPs are determined to be 19.0 % and 4.3 %, respectively. Raman spectroscopy and first‐principles density functional theory calculations verify the sublattice distortion in Cs2 (Na/Ag)BiCl6 DPs via Na + doping. These findings provide fundamental insights into the design of efficient NIR‐emitting Ln 3+ ‐doped DPs for versatile optoelectronic applications. Abstract : A new class of NIR‐emitting lanthanide‐doped double perovskites (DPs) of Cs2 (Na/Ag)BiCl6  : Ln 3+ is proposed. By virtue of the Na + ‐induced breakdown of the local site symmetry, optimal absolute NIR photoluminescence quantum yields of up to 19.0 % and 4.3 % for Yb 3+ and Er 3+, respectively, are achieved in Cs2 Ag0.2 Na0.8 BiCl6 DPs through the effective sensitization of Bi 3+ .